(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Problems posed in problem based learning (PBL) cases used during pre-clinical teaching-framework are typically a set of descriptions of events in need of explanations and resolution. The objectives of this study were to analyze the problems in PBL cases aimed to suggest areas for improvement. Methods: It was a review of cases used in PBL in undergraduate medical curriculum at UKM Medical Centre. Problems in PBL cases were labeled as ‘Triggers’ and ‘Patient Information Sheets’ which were disclosed as prescribed in structured facilitators’ guide. Six of the 10 PBL cases used in semester-1, session 2013-2014 were selected randomly for analysis. Results: Problems in 50% cases were overloaded and in 50% cases sequences of problem-disclosure were disorderly-labeled, though the flow of descriptions were alright. Averagely, 82% faculty-intended learning issues prescribed in facilitators’ guide were connected with problems. Unconnected learning issues were the result of faculty directed teacher-centered approach of guidance, while important learning issues that could have been derived against problems were un-identified. Conclusion: Connectivity of average 82% faculty-intended learning issues with problems reflect as good quality of PBL problems in UKM Medical Centre. However, problem disclosers in disorderly-labeled fashion, unconnected and unidentified issues against some problems in spite of conducting a good numbers of faculty development workshops, raised the issue of needs of further research on standard of training workshops. Educational leaders should give due importance on professionalism and needs of high-quality training for faculty to enhance PBL skills either by utilizing and mobilizing existing properly trained faculty or by hiring appropriate trained faculty. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.417-423